Post-Thaw Viability of Human Fetal Liver Cells of Different Fenotype - Tarasov, A. I.; Petrenko, A. Yu.; Grischenko, V. I.; Jones, D.R. E. (Problems of Cryobiology and Cryomedicine, 2002)
The influence of standard cryopreservation procedure on the viability of different subpopulations of embryonic liver hemopoietic cells was investigated. The viability of cells of the specific phenotype was determined by propidium iodide (PI) staining and labelling with monoclonal antibodies: CD34, CD45, AC133, and Gly-A. The colony-forming activity of human embryonic liver (HEL) suspension was determined by culturing in semisolid medium. The cryopreservation decreases the viability of hemopoietic stem cells (HSC) by 20-30% while the viability of committed erythroid progenitors is decreased by less than 10%. The colony-forming activity of the cryopreserved stem cells demonstrates the validity of the viability values measured. The results obtained testify to the lability of HSC to the effect of low temperatures and appeal for the necessity of an optimisation for their cryopreservation technique.